“You won’t believe what Trump says in this video!”: how young adults authenticate visual information disorder - Holleufer, Sebastian Frederik (2021)
As anybody can bypass the hierarchies of reliable information providers and reach mass audiences via social media, societies are now struggling with information disorder. Although research is critical in order to prevent the spread of information disorder, the dissemination of manipulated imagery is rarely considered even though it is more persuasive than text. This is especially worrying for young adults who primarily depend on social media to stay informed about societal news. As it is unknown whether they are able to withstand the most persuasive form of information disorder, this study hence explores how young adults evaluate the authenticity of digitally shared imagery. Through a combined use of an online survey, semi-structured interviews and focus groups targeting Danes from 15-21 years old, the study finds that young adults are critical of the dangers social media news consumption may entail and generally reluctant to share news online. Although they have a limited ability to detect manipulated imagery, they are not likely to be deceived by visual information disorder as they can use their media literacy skills to analyse the contextual, communicative and/or political factors which surround the manipulated imagery. Ergo, although the field remains largely unexplored, visual information disorder is not as dangerous as previous studies suggest.